IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA MELALUI KEGIATAN ECOPRINT TERHADAP SISWA KELAS V SD NEGERI 2 SUMAMPIR - Aulia Azmi Mardianti (JOIN: Journal of Indonesian Education and Learning, 2026)
This study aims to describe the implementation of the Strengthening of Pancasila Student Profile Project (P5) through ecoprint activities in elementary schools as an effort to strengthen students’ character within the framework of the Merdeka Curriculum. The research employed a qualitative approach with a descriptive method, while data were collected through observation, interviews, and documentation. The research subjects included teachers, the principal, and fifth-grade students of SD Negeri 2 Sumampir, Purwokerto Utara District, Banyumas Regency. The findings reveal that ecoprint activities effectively foster Pancasila Student Profile values, particularly cooperation, independence, creativity, and environmental awareness. The project also enhances students’ collaboration skills, responsibility, and ecological consciousness. Teachers play a crucial role as facilitators in guiding students throughout the process. Overall, the ecoprint project successfully integrates artistic, scientific, and character-building aspects in a balanced manner, making it a contextual learning alternative that supports the development of well-rounded students in line with the objectives of the Merdeka.